Why Does Rem Sleep Occur? A Wake-Up Hypothesis1 - Klemm, Dr. W. R. (Frontiers in Systems Neuroscience, 2011)
Brain activity differs in the various sleep stages and in conscious wakefulness. Awakening from sleep requires restoration of the complex nerve impulse patterns in neuronal network assemblies necessary to re-create and sustain conscious wakefulness. Herein I propose that the brain uses REM to help wake itself up after it has had a sufficient amount of sleep. Evidence suggesting this hypothesis includes the facts that, 1) when first going to sleep, the brain plunges into Stage N3 (formerly called Stage IV), a deep abyss of sleep, and, as the night progresses, the sleep is punctuated by episodes of REM that become longer and more frequent toward morning, 2) conscious-like dreams are a reliable component of the REM state in which the dreamer is an active mental observer or agent in the dream, 3) the last awakening during a night’s sleep usually occurs in a REM episode during or at the end of a dream, 4) both REM and awake consciousness seem to arise out of a similar brainstem ascending arousal system 5) N3 is a functionally perturbed state that eventually must be corrected so that embodied brain can direct adaptive behavior, and 6) corticofugal projections to brainstem arousal areas provide a way to trigger increased cortical activity in REM to progressively raise the sleeping brain to the threshold required for wakefulness. This paper shows how the hypothesis conforms to common experience and has substantial predictive and explanatory power regarding the phenomenology of sleep in terms of ontogeny, aging, phylogeny, abnormal/disease states, cognition, and behavioral physiology. That broad range of consistency is not matched by competing theories, which are summarized herein. Specific ways to test this wake-up hypothesis are suggested. Such research could lead to a better understanding of awake consciousness.